Tradisi ngumbah pusaka di bulan Suro ditinjau dari aspek sosiokultural dan manfaatnya: Studi di Desa Gonggang, Kecamatan Poncol, Kabupaten Magetan - Muhroni, Tedy (Maliki Interdisciplinary Journal, 2023)
The tradition of cleaning heirlooms is one of the traditions carried out to clean the heirlooms inherited from the ancestors in order to expect blessings in life. This tradition contains sociocultural values and various benefits that can be obtained. This research uses a qualitative approach by collecting data through interviews with community leaders and historical stakeholders in Gonggang village, as well as documentation and other literature sources relevant to the topic of discussion. The results of the analysis provide an explanation for the fact that the tradition of cleaning heirlooms carried out by the Gonggang village community during Suro month has a correlation with sociocultural aspects. The tradition of cleaning the Suro month heirlooms can maintain cultural sustainability and preserve the cultural heritage of the ancestors as well as sustainable social interactions in the community, especially in the Gonggang village community. In addition, it also provides benefits that can be a means of education and a form of respect for the ancestors who have passed down this tradition. In conclusion, the tradition of ngumbah pusaka needs to be preserved and maintained because, in addition to providing many benefits, it also maintains the tradition of cleaning heirlooms as a form of cultural sustainability, especially in Javanese culture.